From the prefect’s desk: Gerard van Swieten’s library correspondence - Chlebak, Clara A; Reid, Peter H. (Library and Information History)
This article investigates library-related documents written by Gerard van Swieten (1700–72) during his tenure as Library Prefect in the Imperial Library of Vienna (1745–72). Van Swieten’s time as Library Prefect is considered through a textual analysis. Handwritten letters were deconstructed in terms of their appearance, layout, and tone in order to mine them for meaning. Furthermore, the contents were examined for library matters such as censorship, catalogues, and collection development. The Imperial Court Library held a prominent role as a repository for rare and valuable works, later becoming the National Library of Austria. Gerard van Swieten’s work as a librarian tends to be overlooked, perhaps because he is better known as the private physician of Maria Theresia, as well as a medical reformer. Nevertheless, he was a hard-working chief librarian deeply involved in all aspects of librarianship. Van Swieten endorsed modern scientific works, which were otherwise banned officially by the censorship commission, for the use of scholars in the library, expanded the collection by acquiring books through his network of scholars and publishers, and reissued library catalogues. He also provided for the comfort of users in the library reading room, at a time when such considerations were unusual. In conclusion, a proposal is made that van Swieten viewed his role as librarian with some importance and pride.

Underspecification in deep learning - Bui Thi Mai, Phuong
Deep learning is best known for its empirical success across a wide range of applications spanning computer vision, natural language processing and speech. Of equal significance, though perhaps less known, are its ramifications for learning theory: deep networks have been observed to perform surprisingly well in the high-capacity regime, aka the overfitting or underspecified regime. Classically, this regime on the far right of the bias-variance curve is associated with poor generalisation; however, recent experiments with deep networks challenge this view. This thesis is devoted to investigating various aspects of underspecification in deep learning. First, we argue that deep learning models are underspecified on two levels: a) any given training dataset can be fit by many different functions, and b) any given function can be expressed by many different parameter configurations. We refer to the second kind of underspecification as parameterisation redundancy and we precisely characterise its extent. Second, we characterise the implicit criteria (the inductive bias) that guide learning in the underspecified regime. Specifically, we consider a nonlinear but tractable classification setting, and show that given the choice, neural networks learn classifiers with a large margin. Third, we consider learning scenarios where the inductive bias is not by itself sufficient to deal with underspecification. We then study different ways of ‘tightening the specification’: i) In the setting of representation learning with variational autoencoders, we propose a hand- crafted regulariser based on mutual information. ii) In the setting of binary classification, we consider soft-label (real-valued) supervision. We derive a generalisation bound for linear networks supervised in this way and verify that soft labels facilitate fast learning. Finally, we explore an application of soft-label supervision to the training of multi-exit models.

Empfehlungen für eine nationale Open Science Strategie in Österreich / Recommendations for a National Open Science Strategy in Austria - Mayer, Katja; Rieck, Katharina; Reichmann, Stefan; Danowski, Patrick; Graschopf, Anton; König, Thomas; Kraker, Peter; Lehner, Patrick; Reckling, Falk; Ross-Hellauer, Tony; Spichtinger, Daniel; Tzatzanis, Michalis; et al.
A look at international activities on Open Science reveals a broad spectrum from individual institutional policies to national action plans. The present Recommendations for a National Open Science Strategy in Austria are based on these international initiatives and present practical considerations for their coordinated implementation with regard to strategic developments in research, technology and innovation (RTI) in Austria until 2030. They are addressed to all relevant actors in the RTI system, in particular to Research Performing Organisations, Research Funding Organisations, Research Policy, memory institutions such as Libraries and Researchers. The recommendation paper was developed from 2018 to 2020 by the OANA working group "Open Science Strategy" and published for the first time in spring 2020 for a public consultation. The now available final version of the recommendation document, which contains feedback and comments from the consultation, is intended to provide an impetus for further discussion and implementation of Open Science in Austria and serves as a contribution and basis for a potential national Open Science Strategy in Austria. The document builds on the diverse expertise of the authors (academia, administration, library and archive, information technology, science policy, funding system, etc.) and reflects their personal experiences and opinions.

„Recommendation“ for the further procedure for open access monitoring. Deliverable of the AT2OA subproject TP1-B - Danowski, Patrick; Ferus, Andreas; Hikl, Anna-Laetitia; McNeill, Gerda; Miniberger, Clemens; Reding, Steve; Zarka, Tobias; Zojer, Michael (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare)
As part of the Austrian Transition to Open Access (AT2OA) project, subproject TP1-B is working on designing a monitoring solution for the output of Open Access publications in Austria. This report on a potential Open Access monitoring approach in Austria is one of the results of these efforts and can serve as a basis for discussion on an international level.

Combinatorial width parameters for 3-dimensional manifolds - Huszár, Kristóf
Algorithms in computational 3-manifold topology typically take a triangulation as an input and return topological information about the underlying 3-manifold. However, extracting the desired information from a triangulation (e.g., evaluating an invariant) is often computationally very expensive. In recent years this complexity barrier has been successfully tackled in some cases by importing ideas from the theory of parameterized algorithms into the realm of 3-manifolds. Various computationally hard problems were shown to be efficiently solvable for input triangulations that are sufficiently “tree-like.” In this thesis we focus on the key combinatorial parameter in the above context: we consider the treewidth of a compact, orientable 3-manifold, i.e., the smallest treewidth of the dual graph of any triangulation thereof. By building on the work of Scharlemann–Thompson and Scharlemann–Schultens–Saito on generalized Heegaard splittings, and on the work of Jaco–Rubinstein on layered triangulations, we establish quantitative relations between the treewidth and classical topological invariants of a 3-manifold. In particular, among other results, we show that the treewidth of a closed, orientable, irreducible, non-Haken 3-manifold is always within a constant factor of its Heegaard genus.

(Core Trust) Seal your repository! - Ernst, Doris; Novotny, Gertraud; Schönher, Eva Maria (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare)
A working group, which was established within the Network of Repository Managers (RepManNet), has dealt with common certifications for repositories. In addition, current requirements of the research funding agencies FWF and EU were also taken into account. The Core Trust Seal was examined in more detail. For this purpose, a questionnaire was sent to those organizations that are already certified with CTS in Austria. The answers were summarized and evaluated anonymously. It is recommended to go for a repository certification. Moreover, the development of a DINI certificate in Austria is strongly suggested.

Metabolic regulation of Drosophila macrophage tissue invasion - Emtenani, Shamsi
Metabolic adaptation is a critical feature of migrating cells. It tunes the metabolic programs of migrating cells to allow them to efficiently exert their crucial roles in development, inflammatory responses and tumor metastasis. Cell migration through physically challenging contexts requires energy. However, how the metabolic reprogramming that underlies in vivo cell invasion is controlled is still unanswered. In my PhD project, I identify a novel conserved metabolic shift in Drosophila melanogaster immune cells that by modulating their bioenergetic potential controls developmentally programmed tissue invasion. We show that this regulation requires a novel conserved nuclear protein, named Atossa. Atossa enhances the transcription of a set of proteins, including an RNA helicase Porthos and two metabolic enzymes, each of which increases the tissue invasion of leading Drosophila macrophages and can rescue the atossa mutant phenotype. Porthos selectively regulates the translational efficiency of a subset of mRNAs containing a 5’-UTR cis-regulatory TOP-like sequence. These 5’TOPL mRNA targets encode mitochondrial-related proteins, including subunits of mitochondrial oxidative phosphorylation (OXPHOS) components III and V and other metabolic-related proteins. Porthos powers up mitochondrial OXPHOS to engender a sufficient ATP supply, which is required for tissue invasion of leading macrophages. Atossa’s two vertebrate orthologs rescue the invasion defect. In my PhD project, I elucidate that Atossa displays a conserved developmental metabolic control to modulate metabolic capacities and the cellular energy state, through altered transcription and translation, to aid the tissue infiltration of leading cells into energy demanding barriers.

An Austrian proposal for the classification of Open Access Tuples (COAT) - distinguish different open access types beyond colors - Danowski, Patrick (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare)
In this article a model is described how Open Access definitions can be formed on the basis of objective criteria. The common Open Access definitions such as "gold" and "green" are not exactly defined. This becomes a problem as soon as one begins to measure Open Access, for example if the development of the Open Access share should be monitored. This was discussed in the working group on Open Access Monitoring of the AT2OA project and the present model was developed, which is based on 5 critics with 4 characteristics: location, licence, version, embargo and conditions of the Open Access publication are taken into account. In the meantime, the model has also been tested in practice using R scripts, and the initial results are quite promising.

IST PubRep and IST DataRep: the institutional repositories at IST Austria - Petritsch, Barbara; Porsche, Jana (VÖB Mitteilungen)
In 2013, a publication repository was implemented at IST Austria and 2015 after a thorough preparation phase a data repository was implemented - both based on the Open Source Software EPrints. In this text, designed as field report, we will reflect on our experiences with Open Source Software in general and specifically with EPrints regarding technical aspects but also regarding their characteristics of the user community. The second part is a pleading for including the end users in the process of implementation, adaption and evaluation.

Open Access at IST Austria 2009-2017 - Petritsch, Barbara
Keywords: Open Access; Publication Analysis

An Austrian proposal for the Classification of Open Access Tuples (COAT) - Distinguish different Open Access types beyond colors - Danowski, Patrick

Emerald Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at Emerald from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

IOP Austrian Publications 2012-2015 - Villányi, Márton
Data on Austrian open access publication output at IOP from 2012-2015 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Data Check IOP Scopus vs. Publisher - Villányi, Márton
Comparison of Scopus' and publisher's data on Austrian publication output at IOP.
Keywords: Publication analysis; Bibliography; Open Access

Lizenzverträge mit Open-Access-Komponenten an österreichischen Bibliotheken - Villányi, Márton
Consortial subscription contracts regulate the digital access to publications between publishers and scientific libraries. However, since a couple of years the tendency towards a freely accessible publishing (Open Access) intensifies. As a consequence of this trend the contractual relationship between licensor and licensee is gradually changing as well: More and more contracts exercise influence on open access publishing. The present study attempts to compare Austrian examples of consortial licence contracts, which include components of open access. It describes the difference between pure subscription contracts and differing innovative deals including open access components. Thereby it becomes obvious that for the evaluation of this licence contracts new methods are needed. An essential new element of such analyses is the evaluation of the open access publication numbers. So this study tries to carry out such publication analyses for Austrian open access deals focusing on quantitative questions: How does the number of publications evolve? How does the open access share change? Publications reports of the publishers and database queries from Scopus form the data basis. The analysis of the data points out that differing approaches of contracts result in highly divergent results: Particular deals can prioritize a saving in costs or else the increase of the open access rate. It is to be assumed that within the following years further numerous open access deals will be negotiated. The finding of this study shall provide guidance.

Taylor&Francis Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at Taylor&Francis from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Springer Austrian Publications 2013-2016 - Villányi, Márton
Data on Austrian open access publication output at Springer from 2013-2016 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

SAGE Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at SAGE from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

RSC Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at RSC from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Data Check T&F Scopus vs. FWF - Villányi, Márton
Comparison of Scopus' and FWF's data on Austrian publication output at T&F.
Keywords: Publication analysis; Bibliography; Open Access

Data Check RSC Scopus vs. FWF - Villányi, Márton
Comparison of Scopus' and FWF's data on Austrian publication output at RSC.
Keywords: Publication analysis; Bibliography; Open Access

Implementing the institutional data repository IST DataRep - Barbara Petritsch
In this report the implementation of the institutional data repository IST DataRep at IST Austria will be covered: Starting with the research phase when requirements for a repository were established, the procedure of choosing a repository-software and its customization based on the results of user-testings will be discussed. Followed by reflections on the marketing strategies in regard of impact, and at the end sharing some experiences of one year operating IST DataRep.

Der Springer Compact-Deal – Ein erster Einblick in die Evaluierung einer Offsetting-Vereinbarung - Andrae, Magdalena; Villányi, Márton (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare)
On January the 1st, 2016 a new agreement between 32 Austrian scientific libraries and the publisher Springer took its effect: this deal covers accessing the licensed content on the one hand, and publishing open access on the other hand. More than 1000 papers by Austrian authors were published open access at Springer in the first year alone. The working group "Springer Compact Evaluierung" made the data for these articles available via the platform OpenAPC and would like to use this opportunity to give a short account of what this publishing agreement actually entails and the working group intends to do.

Metadata for research data in practice - Petritsch, Barbara (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen & Bibliothekare)
What data is needed about data? Describing the process to answer this question for the institutional data repository IST DataRep.

Ein freies Bibliothekssystem für wissenschaftliche Bibliotheken – Werkstattbericht der IST Austria Library - Villányi, Márton (Informationspraxis)
Auf der Suche nach einem Bibliothekssystem entschied sich die Forschungseinrichtung IST Austria im Jahr 2014 für das Open-Source-Produkt Koha. In einem ersten Schritt wurden zunächst Grundfunktionen aktiviert um im Anschluss diverse zusätzliche Tools zum Einsatz zu bringen. Die große Flexibilität des Systems erlaubt maßgeschneiderte Lösungen für unterschiedlichste Institutionen. Trotz Herausforderungen kann die Bibliothek auf eine erfolgreiche Implementierung zurückblicken.

Arbeitsgruppe „Nationale Strategie“ des Open Access Network Austria OANA - Bauer, Bruno; Blechl, Guido; Bock, Christoph; Danowski, Patrick; Ferus, Andreas; Graschopf, Anton; König, Thomas; Mayer, Katja; Reckling, Falk; Rieck, Katharina; Seitz, Peter; Stöger, Herwig; et al. (VÖB Mitteilungen)
Based on 16 recommendations, efforts should be made to achieve the following goal: By 2025, all scholarly publication activity in Austria should be Open Access. In other words, the final versions of all scholarly publications resulting from the support of public resources must be freely accessible on the Internet without delay (Gold Open Access). The resources required to meet this obligation shall be provided to the authors, or the cost of the publication venues shall be borne directly by the research organisations.

Notes from Research Data Alliance Plenary Meeting in Dublin, Ireland - Porsche, Jana
Notes from the Third Plenary for the Research Data Alliance in Dublin, Ireland on March 26 to 28, 2014 with focus on starting an institutional research data repository.

Linked (Open) Data - Bibliographische Daten im Semantic Web - Danowski, Patrick; Goldfarb, Doron; Schaffner, Verena; Seidler, Wolfram (VÖB Mitteilungen)
Linked (Open) Data - bibliographic data on the Semantic Web. Report of the Working Group on Linked Data to the plenary assembly of the Austrian Library Network (translation of the title). Linked Data stands for a certain approach to publishing data on the Web. The underlying idea is to harmonise heterogeneous data sources of different origin in order to improve their accessibility and interoperability, effectively making them queryable as a big distributed database. This report summarises relevant developments in Europe as well as the Linked Data Working Group‘s strategic and technical considerations regarding the publishing of the Austrian Library Network’s (OBV’s) bibliographic datasets. It concludes with the mutual agreement that the implementation of Linked Data principles within the OBV can only be taken into consideration accompanied by a discussion about the provision of the datasets under a free license.

(Open) Linked Data in Bibliotheken - Danowski, Patrick; Pohl, Adrian
Das Buch ist sowohl eine Einführung in die Themen Linked Data, Open Data und Open Linked Data als es auch den konkreten Bezug auf Bibliotheken behandelt. Hierzu werden konkrete Anwendungsprojekte beschrieben. Der Band wendet sich dabei sowohl an Personen aus der Bibliothekspraxis als auch an Personen aus dem Bibliotheksmanagement, die noch nicht mit dem Thema vertraut sind.

Initiatives and projects related to RD - Porsche, Jana
This document is created as a part of the project “Repository for Research Data at IST Austria”. It summarises the actual initiatives, projects and standards related to the project. It supports the preparation of standards and specifications for the project, which should be considered and followed to ensure interoperability and visibility of the uploaded data.

Technical requirements and features - Porsche, Jana
This document is created as a part of the project “Repository for Research Data at IST Austria”. It summarises the mandatory features, which need to be fulfilled to provide an institutional repository as a platform and also a service to the scientists at the institute. It also includes optional features, which would be of strong benefit for the scientists and would increase the usage of the repository, and hence the visibility of research at IST Austria.

Kontext Open Access: Creative Commons - Danowski, Patrick (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen & Bibliothekare)
Dieser Artikel soll die sechs verschiedenen Creative Commons Lizenzen erläutern und ihre Bedeutung im Rahmen des wissenschaftlichen Publizierens und des Open Access erklären (CC-BY, CC-BY-SA, CC-BY-NC, CC-BY-ND, CC-BYNC-SA, CC-BY-NC-ND).

Actual state of research data @ ISTAustria - Porsche, Jana
This document is created as a part of the project “Repository for Research Data on IST Austria”. It summarises the actual state of research data at IST Austria, based on survey results. It supports the choice of appropriate software, which would best fit the requirements of their users, the researchers.

Die Zeit des Abwartens ist vorbei! - Danowski, Patrick (BuB - Forum Bibliothek und Information)
Bibliothekare haben die Aufgabe, sich mit neuen Medienformen auseinanderzusetzen.

Zwischen Technologie und Information - Danowski, Patrick (Büchereiperspektiven)
Wie wandelt sich das Berufsbild in Wissenschaftlichen Bibliotheken? Patrick Danowski gibt seine Einschätzung ab.

Computational Topology: An Introduction - Edelsbrunner, Herbert; Harer, John
Combining concepts from topology and algorithms, this book delivers what its title promises: an introduction to the field of computational topology. Starting with motivating problems in both mathematics and computer science and building up from classic topics in geometric and algebraic topology, the third part of the text advances to persistent homology. This point of view is critically important in turning a mostly theoretical field of mathematics into one that is relevant to a multitude of disciplines in the sciences and engineering. The main approach is the discovery of topology through algorithms. The book is ideal for teaching a graduate or advanced undergraduate course in computational topology, as it develops all the background of both the mathematical and algorithmic aspects of the subject from first principles. Thus the text could serve equally well in a course taught in a mathematics department or computer science department.

Handbuch Bibliothek 2.0
With the term "Library 2.0" the editors mean an institution which applies the principles of the Web 2.0 such as openness, re-use, collaboration and interaction in the entire organization. Libraries are extending their service offerings and work processes to include the potential of Web 2.0 technologies. This changes the job description and self-image of librarians. The collective volume offers a complete overview of the topic Library 2.0 and the current state of developments from a technological, sociological, information theoretical and practice-oriented perspective.

Ist Bibliothek 2.0 überhaupt noch relevant? – Eine Einleitung in das Handbuch - Bergmann, Julia; Danowski, Patrick (Handbuch Bibliothek 2.0)
Mit diesem Buch möchten wir einen Überblick der aktuellen Diskussion zum Thema Bibliothek 2.0 geben und den Stand der tatsächlichen Umsetzung der Web 2.0-Ansätze in deutschsprachigen Bibliotheken beleuchten. An dieser Stelle ist die Frage erlaubt, warum es zu einer Zeit, in der es bereits die ersten "Web 3.0"- Konferenzen gibt, eines Handbuches der Bibliothek 2.0 noch bedarf. Und warum es überhaupt ein deutschsprachiges Handbuch zur Bibliothek 2.0 braucht, wo es doch bereits verschiedenste Publikationen zu diesem Thema aus anderen Ländern, insbesondere des angloamerikanischen Raums gibt. Ist dazu nicht bereits alles gesagt?

Elektrowiz – system of measurement data management - Zubielik, Piotr; Nadaczny, Jerzy; Krzysztof Pietrzak; Lawenda, Marcin (Przeglad Elektrotechniczny)
Large amount of data management can cause a lot of troubles which can be solved by dedicated computer system. To facilitate management of measurement data which are gathered in Institute of Power Engineering - Insulation Department a special system called Elektrowiz® was developed. It allows storing measurement results which concern partial discharges in insulation of turbo- and hydrogenerators in power stations. Multilayer architecture of the system allows reaching gathered data independently on user localization. There are possible different access methods to the system and dependency on current requirements data exploration can be realized with read-only or edit rights.

Spatiogram-based shot distances for video retrieval - Ulges, Adrian; Christoph Lampert; Keysers,Daniel
We propose a video retrieval framework based on a novel combination of spatiograms and the Jensen-Shannon divergence, and validate its performance in two quantitative experiments on TRECVID BBC Rushes data. In the first experiment, color-based methods are tested by grouping redundant shots in an unsupervised clustering. Results of the second experiment show that motion-based spatiograms make a promising fast, compressed-domain descriptor for the detection of interview scenes.